YammerAds: Instant Access to Reliable and Affordable Advertising Services - Bhaskar, T; Patil, VK; Ghumare, MS; Aher, AV (International Journal of Computer Sciences and Engineering, 2025)
Advertising has seen tremendous growth in recent years. Lot of companies, organizations, small and large businesses, from simple app to big ventures wants to advertise and open themselves in front of the world. Today Advertising firms and customers facing many problems such as lack of brand advertiser availability, Sales and operational inefficiency, Ineffective creative formats, Wrong display target for Premium Advertisements etc. To remove all the barriers and limitations we are going to implement a project called YammerAds: Instant Access to Reliable and Affordable Advertising Services. This system is a platform for Businesses and Advertising service providers based on different locations. The system will explore appropriate service providers for businesses and individual customers at different locations along with their details of key-services, cost plans, showcases. YammerAds provides genuine service providers to users who want to publish advertisements for their brands, so they can easily work with remote service providers to explore their business through advertising.